Periodontite em indivíduos com psoríase e artrite psoriásica: aspectos clínicos, microbiológicos, imunológicos e qualidade de vida relacionada a saúde bucal - Amanda Almeida Costa (2024)
Increasing evidence suggests an association among psoriasis (PSO), psoriatic arthritis (PsA), and periodontitis (PE), as suggested for other systemic diseases. Two studies were carried out: (I) case-control to evaluate the oral impacts (OHRQOL) on daily activities in individuals with psoriatic disease compared to non-psoriatic patients and (II) evaluate the levels of Porphyromonas gingivalis, Treponema denticola, Tanerella forsythia, Aggregatibacter actinomycetemcomitans and quantify the salivary biomarkers RANKL, OPG, survivin and IL-17 in individuals with PSO and PsA, compared to non-psoriatic individuals with and without PE. Study I: included 296 individuals (PSO n= 210, PsA n= 86) as cases and 359 without psoriatic disease (control). Complete periodontal examinations were performed, variables of interest were collected and the Brazilian version of the Oral Impacts on Daily Performance (OIDP) instrument was applied. The prevalence of PE was higher in PsA (57.0%; OR=2.67.95%CI :1.65-4.32; p<0.001) than in PSO (34.3%; OR=1.05;0.73-1.51; p<0.001) compared to controls (33.1%). Both PsA and PSO exhibited more sites and teeth with probing depth (PD) of 4-6mm than controls (p<0.001). Analyzing OHRQoL, PsA and PSO had higher OIDP scores than controls (p<0.001), indicating worse self reported quality of life. In the influence of variables of interest on quality of life (QoL), PE, psoriasis+PE and alcohol/anxiolytics intake were significant (p<0.05). The influence of periodontal parameters on QoL was observed for the presence of PE; PD > 6mm; clinical attachment level >6mm; > plaque index, >% sites and teeth with bleeding on probing (p=0<0.05). This study demonstrated the negative impacts of PE on the OHRQOL of the individuals analyzed, with individuals with PSO and especially PsA and PE presenting significantly worse OHRQOL indicators. Study II: based on study I, 192 non-smoking and non-diabetic individuals were randomly selected, matched by gender and allocated into 6 groups (control, PSO and PsA, with and without PE; n=32 per group). The results revealed higher counts of P. gingivalis, T. forsythia and T. denticola in the groups with PE compared to without PE (p<0.05). Higher counts of these periodontopathogens were observed in the PsA with PE group followed by PSO with PE when compared to controls. Additionally, there were significant intergroup differences in the levels of RANKL (p=0.039), IL-17 and survinin (p<0.001) (PsA>PSO>Controls). In individuals with PsA and PE, the levels of OPG, IL 17 and survinin were significantly higher than in PsA without PE. Positive correlations between RANK-L, IL-17 and survinin and negative correlations for OPG were observed in relation to all periodontal clinical parameters analyzed (p<0.001). It was concluded that individuals with psoriatic disease and PE had significantly worse microbiological conditions and higher levels of the studied biomarkers, with these results being even more significant in individuals with PsA and PE.